Pharmacokinetic, Clinical, and Myeloid Marker Responses to Acepromazine Sedation in Arabian Camels - Kandeel, Mahmoud; Almubarak, Adel I.; Hussen, Jamal; El-Deeb, Wael; Venugopala, Katharigatta N. (Frontiers in Veterinary Science, 2021)
Sedatives and tranquilizers are important in the control of excited camels during camel transport. This study was conducted to investigate the clinical sedation of camels with acepromazine and its correlation with pharmacokinetics and pharmacodynamics. The sedation score, heart rate, respiration, body temperature, and pharmacokinetics were monitored before and after acepromazine injection, and myeloid marker expression was analyzed using membrane immunofluorescence and flow cytometry. The distribution (t1/2α) and elimination (t1/2β) half-lives were 0.1 and 9.4 h, respectively. The volume of distribution at steady state (Vss) was 20.01 L/kg, and the mean residence time (MRT) was 12.25 h. Sedation started rapidly within 10 min followed by persistent low-medium sedation for 2 h with an average sedation score of 1.2 ± 0.61, which might be associated with a slow elimination phase and prolonged MRT. Compared to horses, camels showed a lower clearance rate, higher volume of distribution, and higher elimination half-life. Slight changes in body temperature and heart and respiratory rate, as well as a lower hematocrit and changes in blood cell composition, suggest the careful application of acepromazine in animals with abnormal blood parameters or poor vital conditions.